Impact of an Extreme Typhoon Event on Subsequent Sediment Discharges and Rainfall-Driven Landslides in Affected Mountainous Regions of Taiwan - Ching Hung; Guan-Wei Lin; Hsien-Li Kuo; Jia-Ming Zhang; Chi-Wen Chen; Hongey Chen (Geofluids)
Fluctuations in the sediment yielding rate within mountainous areas are found after extreme precipitations. These changes are associated with rainfall-driven landslides and can be evaluated through observations of sediment transported in river water. In this study, we assess the differential impact level and duration of an extreme rainfall event caused by the 2009 Typhoon Morakot in Taiwan. Using a time series of suspended sediment data and landslide inventories within three affected catchments, our results found that the proportion of the typhoon-generated sediment discharges reached 58% of the 2009 annual sediment discharges, and the annual sediment discharges could be 15-fold higher than the average annual sediment discharges prior to the typhoon. The impact of the typhoon on suspended sediment discharge lasted for around four months. It is further revealed that a significant increase in the number of landslides was attributed to the impact of the extreme typhoon event, and the critical rainfall condition triggering landslides, based on the relationship between rainfall and landslide number and the rainfall intensity-duration thresholds, declined for 4–5 years.